Increasing Public Knowledge About Tuberculosis Through The Healthy Movement Without Tb (Gesat-Tbc) Program In Kasang Pudak Village - Esra Simamora; Rizka Apriliana; Siti Aisyah; Fadhil Abdulla; Ester Laura (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Intoduction: Tuberculosis (TBC) remains one of the major public health problems in Indonesia, with the incidence rate increasing each year. low level of public knowledge regarding TBC prevention and treatment contributes to the low achievement of TBC elimination at the community level.. Method: This study employed a quantitative approach with a cross-sectional design, involving 40 respondents selected using the Slovin formula. Data were collected using pre-test and post-test questionnaires conducted before and after educational intervention on TBC. The data were analyzed using the Wilcoxon test.The results showed that 22 respondents experienced an increase in knowledge scores, while two respondents showed a decrease and two remained unchanged. The Wilcoxon test yielded a significant result (p-value = 0.000), indicating that educational interventions significantly improved the community’s knowledge regarding TBC. Result and Discussion: Prior to the intervention, most respondents had a low level of knowledge (47.5%), but after the intervention, there was an increase toward moderate and high levels.In conclusion, the educational intervention program “Edukasi GESAT-TBC” effectively enhanced community knowledge and awareness regarding tuberculosis prevention and control in Kasang Pudak Village.. Conclusion: This program is expected to serve as a sustainable health education effort that supports the government’s target of TBC elimination by 2030 through promotive and preventive community-based approaches.